Factors Influencing Bridge Inspection in Developing Countries, Challenges and Future Directions: A Systematic Literature Review - Arshad, Tuba; Andhika Karim, Dr. Rully; Rarasati, Ayomi Dita (Smart City, 2024)
Bridges are very important to promote economic growth, mitigate poverty, and address persistent environmental issues. With the construction of new bridges, it is crucial to have an effective bridge inspection procedure. But most developing countries are still struggling in this field. This review examines common factors affecting bridge inspection in developing countries and their impact on bridge condition and performance while exploring strategies to improve those factors in developing countries in a systematic review. A total of 172 articles were identified through an explorative search of Direct Scopus, Google Scholar, and hand-search with limitations of the years 2013 to 2024. Only 15 articles were considered and classified based on the related topic of research study and keywords, such as Inspection of infrastructure, Improvement of bridge inspection, maintenance, and developing countries related articles. The findings from previous research studies show that the factors budget, resources, policies/Laws/regulations, Bridge age, and transparency are the factors that influence bridge inspection practices in developing countries. It is important to work on these factors to improve bridge inspection in developing countries. The recommendations from previous studies that can improve these factors are exploring new funding sources, enhancing the training programs, introducing cutting-edge technologies, updating standard guidelines every year, developing a centralized online portal to give regular updates of inspection data, and advocating for long-term planning. Therefore, this analysis concludes that bridge inspection practices can be improved in developing countries by improving all those factors.